Principles of managerial finance - Gitman, Lawrence J.; Zutter, Chad J. (Prentice Hall series in finance, 2012)
This text weaves pedagogy into concepts and practice, providing students with a road map to guide them through the text and supplementary tools. The 13th edition now includes an emphasis on personal finance issues to add currency and relevance to the already cohesive learning framework.